Clinical and Genetic Profile of X-Linked Agammaglobulinemia: A Multicenter Experience From India - Rawat, Amit; Jindal, Ankur Kumar; Suri, Deepti; Vignesh, Pandiarajan; Gupta, Anju; Saikia, Biman; Minz, Ranjana W.; Banday, Aaqib Zaffar; Tyagi, Rahul; Arora, Kanika; Joshi, Vibhu; Mondal, Sanjib; et al. (Frontiers in Immunology, 2021)
Background: There is paucity of literature on XLA from developing countries. Herein we report the clinical and molecular profile and outcome in a multicentre cohort of patients with XLA from India. Methods: Data on XLA from all regional centres supported by the Foundation for Primary Immunodeficiency Diseases (FPID), USA and other institutions providing care to patients with PIDs were collated. Diagnosis of XLA was based on European Society for Immunodeficiencies (ESID) criteria. Results: We received clinical details of 195 patients with a provisional diagnosis of XLA from 12 centres. At final analysis, 145 patients were included (137 ‘definite XLA’ and 8 ‘probable/possible XLA’). Median age at onset of symptoms was 12.0 (6.0, 36.0) months and median age at diagnosis was 60.0 (31.5, 108) months. Pneumonia was the commonest clinical manifestation (82.6%) followed by otitis media (50%) and diarrhoea (42%). Arthritis was seen in 26% patients while 23% patients developed meningitis. Bronchiectasis was seen in 10% and encephalitis (likely viral) in 4.8% patients. Pseudomonas aeruginosa was the commonest bacterial pathogen identified followed by Streptococcus pneumoniae, Staphylococcus aureus and Klebsiella pneumoniae. Molecular analysis revealed 86 variants in 105 unrelated cases. Missense variants in BTK gene were the most common (36%) followed by frameshift (22%) and nonsense variants (21%). Most pathogenic gene variants (53%) were clustered in the distal part of gene encompassing exons 14-19 encoding for the tyrosine kinase domain. Follow-up details were available for 108 patients. Of these, 12% had died till the time of this analysis. The 5-year and 10-year survival was 89.9% and 86.9% respectively. Median duration of follow-up was 61 months and total duration of follow-up was 6083.2 patient-months. All patients received intravenous immunoglobulin (IVIg) replacement therapy. However, in many patients IVIg could not be given at recommended doses or intervals due to difficulties in accessing this therapy because of financial reasons and lack of universal health insurance in India. Hematopoietic stem cell transplant was carried out in 4 (2.8%) patients. Conclusion: There was a significant delay in the diagnosis and facilities for molecular diagnosis were not available at many centres. Optimal immunoglobulin replacement is still a challenge